2017
DOI: 10.5194/acp-17-12405-2017
|View full text |Cite
|
Sign up to set email alerts
|

Mobile measurement of methane emissions from natural gas developments in northeastern British Columbia, Canada

Abstract: Abstract. North American leaders recently committed to reducing methane emissions from the oil and gas sector, but information on current emissions from upstream oil and gas developments in Canada are lacking. This study examined the occurrence of methane plumes in an area of unconventional natural gas development in northwestern Canada. In August to September 2015 we completed almost 8000 km of vehicle-based survey campaigns on public roads dissecting oil and gas infrastructure, such as well pads and processi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 27 publications
5
79
1
Order By: Relevance
“…The survey data was analyzed to isolate CH 4 -rich plumes from the varying ambient atmospheric levels using ratios of super-ambient (or 'excess', denoted by 'e') CO 2 and CH 4 (eCO 2 :eCH 4 ). The gas ratio approach has been used previously by Atherton et al (2017), Williams et al (2018), andO'Connell et al (2019), though the most complete explanation is presented in Hurry et al (2016). Ambient atmospheric CO 2 and CH 4 vary spatiotemporally due to factors such as atmospheric stability, land-use types, and topography.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The survey data was analyzed to isolate CH 4 -rich plumes from the varying ambient atmospheric levels using ratios of super-ambient (or 'excess', denoted by 'e') CO 2 and CH 4 (eCO 2 :eCH 4 ). The gas ratio approach has been used previously by Atherton et al (2017), Williams et al (2018), andO'Connell et al (2019), though the most complete explanation is presented in Hurry et al (2016). Ambient atmospheric CO 2 and CH 4 vary spatiotemporally due to factors such as atmospheric stability, land-use types, and topography.…”
Section: Methodsmentioning
confidence: 99%
“…To account for these natural variations, the method considers the minimum value of each gas within a moving time window to be representative of background levels for that part of the survey. The size of the window is optimized for each survey to account for the respective level of variance (Atherton et al 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relevant lessons include (i) identification of major emission sources across the natural gas supply chain Zimmerle et al, 2015;Marchese et al, 2015), (ii) proof that high-emitting sources disproportionately account for the majority of emissions (Brandt et al, 2014;Brandt et al, 2016;Omara et al, 2016;Lyon et al, 2016;Zavala-Araiza et al, 2017), and (iii) examples of smart regulations significantly reducing emissions from different sources (e.g., green completions, replacement of high-emitting pneumatic controllers) (Allen et al, 2013;. With a limited number of studies reporting empirical observations of oil and gas methane emissions outside the US -and specifically in Canada - (Johnson et al, 2017;Atherton et al, 2017) the question remains about whether the same emission characteristics found in the US apply elsewhere.…”
Section: Introductionmentioning
confidence: 99%